PEMBATALAN HIBAH PERSPEKTIF HUKUM ISLAM DAN KUHPER DI DESA KEDUNGDOWO KECAMATAN ARJASA SITUBONDO - Ahmad Muzayyin; Mawardi Mawardi; Syarifuddin Syarifuddin (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2022)
In this study, the author will present a unique phenomenon about the marriage process in Kedungdowo Village, Arjasa District, Situbondo. In this society, when getting married, the groom will bring a set of household tools to present to the prospective bride. This is not a request from the bride but because of the customary factor. The items they carry are very many such as chairs, tables, cupboards, and others. Then the concern of the researcher is when their marriage relationship breaks up in the middle of the road or is divorced then what happens? Before we continue the results of this study, that this research is field with a qualitative approach. The focus of the discussion is how the above incident is viewed from the perspective of Islamic law and positive law or the Civil Code. And in extracting the data sources of researchers Then in looking for data sources, the authors use primary data sources in the form of: observations, interviews, and documentation. And the author will also optimize secondary data, namely additional data such as from books, books and others. From the analysis and studies conducted by the researchers, it can be concluded that: In Islamic law, it is permissible to withdraw the property given by a husband to his wife after a divorce in Kedungdowo Village, Arjasa Situbondo District, because the gift does not include a grant. And in Positive law, grants may be withdrawn if they have fulfilled the three things mentioned in the Civil Code article 1688.